ALANG DAN DEDAP DURHAKA: KAJIAN INTERTEKSTUAL - Wahyuni, Sri; ', Elmustian; ', Hermandra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstracts: Intertextual study as a search effort meaning continuously. So, this study aims to see how the structure of the Alang Story Story and Dedap Ungodly Story, as well as on how the intertextual transformation of these two points. This study is a qualitative study with descriptive form, done with a) reduction, b) classification, c) display, and d) performing interpretations and taking conclusions. The results of the study were conducted through structural text transformation analysis with cultural and historical approach. The analysis of the study showed that TCA as a TCDD hypogram. The equations found in the plot, characterization, background, theme and point of view of both stories indicate an intertextual relationship. The implications of this study are for the creation of new literary works for writers and researchers in analyzing intertext relationships.Key Words: Intertextual, transformation, TCA, TCDD, structural.